A Polymer-based Drilling Fluid with High Temperature, Salt and Calcium Resistance Property. Issue 5 (February 2019) - Dai, Zhiwen; Sun, Jinsheng; Wang, Yan
Abstract: Filtrate reducer is facing higher requirements and challenges in temperature and salt resistance. A novel polymer filtrate reducer was synthesized by free radical polymerization in aqueous solution. By filtration experiments, the results show that the polymer has good filtration loss performance under high temperature and saturated salt. Through the optimization with filtrate reducer and inhibitor, the optimum components of drilling fluids are water, 4.0wt% bentonite, 0.3wt% Na2 CO3, 2.0wt% DAADS, 3.0wt% SMP-II, 3.0wt% SPNH, 3.0wt% SMC, 1.0wt% SDJA and 2.0wt% RH-3. The drilling fluid system has temperature resistance up to 220°C, salt resistance to saturation and calcium resistance up to 1.0%. The API fluid loss of the drilling fluids with the addition of saturated NaCl and 1wt% CaCl2 respectively after aging at 220°C was 6.0 mL and 4.4 mL.